Home grown honkers. - Dill, Herbert H; Lee, Forest B., joint author.; United States. Bureau of Sport Fisheries and Wildlife. ([Washington, U.S. Dept. of the Interior, Fish and Wildlife Service, Bureau of Sport Fisheries and Wildlife, 1970)
Includes bibliography. Mode of access: Internet.